Thinking outside the box: Turkish EFL teachers' perceptions of creativity - Akyildiz, Secil Tumen; Celik, Vildan (Elsevier Sci Ltd, 2020)
Creativity is one of the essential 21st-century skills that need to be developed in students because we are living in an age that is ever-changing and unpredictable. Students should be encouraged to think outside the box not only through subjects like art, music, science, literature, etc. but also in educational settings like English as a foreign language (EFL) classes. Teachers certainly have the most significant role in fostering students' creative thinking abilities by implementing creative teaching in their lessons. Thus, the aim of the study is to explore the perceptions of Turkish EFL teachers about creativity and their creative teaching practices. It was designed as a qualitative research; interviews were held to probe in-depth into their perceptions on creativity. In line with the aim of the study, the research questions were determined as follows: 1) What does creativity mean to Turkish EFL teachers? 2) What kind of creative teaching activities do Turkish EFL teachers utilize in their classrooms? 3) What are the factors affecting creative teaching and learning? As the instrument, an interview form was prepared to collect data by reviewing relevant literature and consulting the specialists' views. The researchers conducted interviews with fifteen secondary school EFL teachers, chosen randomly. They participated in research from different schools voluntarily. The participants were selected regarding their schools' socio-economic position, their experience, gender and age to prove a general perspective of creativity. The data obtained from the interviews were analyzed through qualitative content analysis. The findings have revealed that the majority of the teachers are not aware of the central philosophy of creativity, and they do not apply a creative approach in their teaching. However, it is indicated that they use several activities in their classrooms like brainstorming, games, snap-words, and storytelling to encourage creativity. It is emphasized that there are factors constraining creativity and their creative teaching practices such as content-heavy curriculum, exam-oriented education, students, limited course duration and technology. On the other hand, there are factors facilitating creativity, like teacher motivation, technology and students. It is worth noting that 'technology' and 'students' were addressed both as facilitating and constraining factors. This study explored the perceptions of Turkish EFL teachers about creativity and their creative teaching practices. It is hoped to contribute to the field with valuable results.
Keywords: Creativity; Creative thinking; Creative teaching; EFL; Teacher perception